Concurrent sketching model for the industrial product conceptual design (2014)
Conceptual design is one of the earliest stages of product development, and is responsible for defining key aspects of the final product. The systematic approach addresses this stage by using a disaggregate model of product attributes and their corresponding geometries. This ultimately serves as a starting point for exploring conceptual proposals. Research into the emergence of various sketch typologies shows that they are labeled according to aim rather than technical utility. The proposed sketch-based model is intended to serve as a comprehensive version of the systematic model for conceptual design (Hernandis and amp; Briede, 2009). Sketch outlines are used during various stages of the model in order to enable and visually assist with cognitive processes and decision-making during the initial theoretical stages, which are abstract and poorly defined.